2020
DOI: 10.1136/jitc-2020-001626
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming leukemia heterogeneity by combining T cell engaging bispecific antibodies

Abstract: BackgroundLeukemia represents about 5% of all human cancers. Despite advances in therapeutics, a substantial number of patients succumb to the disease. Several subtypes of leukemia are inherently more resistant to treatment despite intensive chemotherapy or targeted therapy.MethodsHere we describe the generation of T cell engaging (CD3) bispecific antibodies (BsAbs) built on humanized IgG frameworks using the IgG(L)-scFv format against two targets expressed on acute lymphoblastic leukemia (ALL) and on acute my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Another potential mechanism of resistance is the possibility of a myeloid lineage switch following blinatumomab therapy, particularly in KMT2A(MLL)-rearranged ALL, which may lead to the development of AML [ 89 , 90 , 91 , 92 ]. A recent preclinical study evaluated the possibility of combining anti-CD19 and anti-CD33 BiAbs to target tumor heterogeneity and prevent clonal escape [ 93 ].…”
Section: Bispecific T-cell Engagers and Antibodies In The Treatment O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential mechanism of resistance is the possibility of a myeloid lineage switch following blinatumomab therapy, particularly in KMT2A(MLL)-rearranged ALL, which may lead to the development of AML [ 89 , 90 , 91 , 92 ]. A recent preclinical study evaluated the possibility of combining anti-CD19 and anti-CD33 BiAbs to target tumor heterogeneity and prevent clonal escape [ 93 ].…”
Section: Bispecific T-cell Engagers and Antibodies In The Treatment O...mentioning
confidence: 99%
“…Another potential mechanism of resistance is the possibility of a myeloid lineage switch following blinatumomab therapy, particularly in KMT2A(MLL)-rearranged ALL, which may lead to the development of AML [89][90][91][92]. A recent preclinical study evaluated the possibility of combining anti-CD19 and anti-CD33 BiAbs to target tumor heterogeneity and prevent clonal escape [93]. (2) myeloid lineage switch after blinatumomab therapy, which has been reported in cases of KMT2A(MLL)-rearranged acute lymphoblastic leukemia, resulting in the development of acute myelogenous leukemia; (3) the immunosuppressive microenvironment in acute lymphoblastic leukemia is associated with an increased percentage of regulatory T cells along with a lower frequency of CD8+/CD3+ T cells, thereby facilitating resistance to blinatumomab.…”
Section: Bispecific T-cell Engagers and Antibodies In The Treatment O...mentioning
confidence: 99%
“…In diffuse large B-cell lymphoma patients, 56% demonstrated a response to blinatumomab ( Topp et al., 2011 ; Suresh et al., 2014 ). Other studies are being done to find other promising bispecific antibodies for leukemia and lymphoma, and the CD19-specific bispecific antibody (BC250) was found more effective than blinatumomab against ALL xenografts in vivo ( Hoseini et al., 2020 ).…”
Section: Immunotherapy Strategies For Hematological Cancer Treatmentmentioning
confidence: 99%
“…Given the presence of different lineage antigens in MPAL, it is thought that bi-specific immunotherapy options might be more efficacious. Pre-clinical data have shown that dual-targeting triplebody therapy directed against CD33/CD3/CD19 leads to selective and effective lysis of biphenotypic B/myeloid cells expressing CD19 and CD33 [ 82 , 83 ]. A recent case report successfully utilized two immunotherapy options targeting separate antigens (Blinatumomab for CD19 and Gemtuzumab for CD33) to successfully treat a refractory, KMT2A-rearranged infant MPAL [ 37 ].…”
Section: Novel Approachesmentioning
confidence: 99%